PEMANFAATAN LIMBAH AIR KELAPA MENJADI NATA DE COCO UNTUK MENINGKATKAN PENDAPATAN PEDAGANG KELAPA PARUT - Ekawati, Ekawati; Rizieq, Rahmatullah; Ellyta, Ellyta (LPPM UNS, 2014)
In general, the aims of the service to the community program is to provide the training of the wastewater treatment in making nata de coco to the coconut traders in Dahlia traditional markets that can provide them an additional income. The specific aims are : (1) To give the grated coconut trader and their partner knowledge about the processing of nata de coco, (2) To give the coconut traders and their partners knowledge of processing nata de coco into various flavors, (3) To share the coconut traders and their partners the knowledge about how to package so that it will become more attractive, Finally (4) To improve their management and to expand their marketing network.Methods are used: (1) Dissemination knowledge of nata de coco, (2) Counseling and training wastewater treatment of the coconut into nata de coco for the coconut trader and their partners in the Dahlia, traditional market town in Pontianak, (3) Improving the quality of human resources, And (4) Training Product Promotion of SMEs through the Internet.The results show that the interest of participants to the activities of is very large. This is demonstrated by the sight of people exiting to follow and pay attention in any of the material presented, as well as their desire to know more about the process of nata de coco. Based on the aggregate information that is collected by the team that one of the key success of the implementation of this activity is their desire to earn more income, furthemore due to the abundant of the raw material for making nata de coco in their environment.